Ten little unicorns - Mike Brownlow (London; Orchard Books, 2022)
It's Princess Petal's birthday, but - oh no! - her cake is nowhere to be seen! Can ten brave little unicorns find the missing cake in time for the royal birthday party? Follow the ten little unicorns as they venture through an enchanted land, meeting witches, wizards, dragons, and fairies along the way. Read the bouncy rhyming story and count from ten to one and back again, as the little unicorns disappear then reappear. Spot and count the details on each page, and join in with the magical read-aloud sounds
Keywords: Board books